Improving Poetry Writing Skills Through a Project-Based Learning Model Assisted by Powtoon Media for Students of Public Vocational High School 6 Surakarta - Hartanti, Hestik; Miftakhul Huda; Rahmawati, Murtini (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
This study aims to improve the ability to create poetry using a project-based learning approach by utilizing Powtoon media for students at the State Vocational High School 6 Surakarta. This research is a classroom action carried out in two cycles using a project-based learning model. The research was conducted at the State Vocational High School 6 Surakarta and involved 36 students of class X AKL 3 Phase E. Research data were obtained through observation, student work, and learning videos. Data collection was carried out through individual tests and observations using skill tests as research instruments. Data validation was carried out using triangulation techniques and data analysis used qualitative and quantitative approaches. The results of the two cycles of this study show that the use of a project-based learning model with Powtoon media can improve students' poetry writing skills at SMK N 6 Surakarta. Through this project-based learning approach, the ability to write poetry can be improved with the help of Powtoon media, students' creativity in writing poetry also increases, creating more creative audio visual products or animated videos.